Rheological Characterization And Fouling Mitigation Of Coconut Cream Emulsion - Maghazechi, Avan Farouq Qadir (2023)
This study aimed to understand and mitigate fouling deposition in CCE by investigating structural changes in heating surfaces and CCE bulk.